(untitled) (Cantho, 2005)
This book introduction and explain the purpose of electrical symbols and drawings, list three main categories of electrical symbols and drawing, indentify and draw from memory some common electrical symbols
Keywords: English language,Tiếng anh; Electrical engineering,Công nghệ điện